Clinical management of the adult with Parkinson's disease. - Smolowitz J; Waters C (American Journal for Nurse Practitioners)
Parkinson's disease (PD) is the third most common neurologic disorder of the elderly, after stroke and Alzheimer's disease. The population of the United States is aging. It is projected that by 2020, the number of people over age 65 will have doubled compared to the number in 1990 and that by 2030, 20% of the United States population, or 70,000,000 people, will be over age 65. As the population of the United States continues to age, nurse practitioners (NPs) can expect to provide care for adults with PD. Recent advances in treatment modalities have improved the quality of life for individuals with this disease. This article discusses standardized patient assessment instruments acrd therapeutic modalities currently used to treat PD. The underlying pathophysiologic process is reviewed as it forms tire basis for treatment.